2009
DOI: 10.1097/hjh.0b013e32833105a6
|View full text |Cite
|
Sign up to set email alerts
|

Improving cardiovascular risk stratification in essential hypertensive patients by indexing left ventricular mass to height2.7

Abstract: Our data indicate that a consistent portion of essential hypertensive patients are positive for LVH by the criterion of LVM indexed to height(2.7), but not to BSA; this population is characterized by an unhealthy metabolic profile as well as by the presence of extracardiac organ damage. They also suggest that, in order to improve cardiovascular stratification, LVM should be routinely indexed to both BSA and height(2.7) and patients categorized according to the consistency of both criteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 26 publications
2
18
0
Order By: Relevance
“…It has been observed that in patients treated with astatines cardiovascular risk has not been reduced when HDL remains low [64]. Elevated levels of uric acid was a risk factor for hypertensive cardiopathy, and some studies [33,55], coincide with our indings.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…It has been observed that in patients treated with astatines cardiovascular risk has not been reduced when HDL remains low [64]. Elevated levels of uric acid was a risk factor for hypertensive cardiopathy, and some studies [33,55], coincide with our indings.…”
Section: Discussionsupporting
confidence: 81%
“…As in the present series, Cuspidi [55] and Yeboah [63], did not ind any nonindependent association between high levels of triglycerides and the risk of LVH.…”
Section: Discussionsupporting
confidence: 65%
“…For the latter there is currently an index designed in our context, consisting on a multivariate study, based on a case-control study [24]. Although the study showed an adequate internal and external validity [24], it is necessary to improve it based on the fact that the risk of developing depends not only on multiple causes but also with permanent evolutional changes, as has been demonstrated by several studies [21,[24][25][26][27][28][29]. Another aspect to highlight is that the Hosmer and Lemeshow Test X 2 = 5.059 degrees of freedom 8 p = 0.0751. new proposal is based on a cohort study, which have demonstrated a better capacity to predict risks.…”
Section: Discussionmentioning
confidence: 99%
“…LVM was indexed separately for BSA (LVMI/BSA) and height (LVMI/height 2.7 ). Thus, patients were diagnosed with LVH based on two separate criteria: LVMI/BSA > 110 g/m 2 for women and >134 g/m 2 for men [20] or LVMI/height 2.7 > 45 g/m 2.7 for women and >49 g/m 2.7 for men [21]. …”
Section: Methodsmentioning
confidence: 99%